1984
DOI: 10.1007/bf00485854
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic mutants of Chinese hamster cells with altered cytidine 5?-triphosphate synthetase

Abstract: Following chemical mutagenesis and multiple-step indirect selection, four clones of Chinese hamster V79 cells were isolated which exhibited auxotrophy for thymidine, deoxycytidine, or deoxyuridine but not for cytidine or uridine. All were resistant to uridine, 3-deazauridine, 5-fluorouridine, thymidine, and cytosine arabinoside at concentrations that were toxic to wild-type V79 cells. The cytidine 5'-triphosphate (CTP) and deoxycytidine 5'-triphosphate (dCTP) pools in the mutants were expanded, but the uridine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
(26 reference statements)
4
20
0
Order By: Relevance
“…Concluding Discussion-The level of CTP synthetase activity plays an important role in the growth and metabolism of S. cerevisiae (5,6,9), as well as in higher eukaryotic organisms (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). In this study, we demonstrated that the URA7-encoded CTP synthetase was phosphorylated and stimulated by protein kinase A.…”
Section: Figmentioning
confidence: 61%
“…Concluding Discussion-The level of CTP synthetase activity plays an important role in the growth and metabolism of S. cerevisiae (5,6,9), as well as in higher eukaryotic organisms (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). In this study, we demonstrated that the URA7-encoded CTP synthetase was phosphorylated and stimulated by protein kinase A.…”
Section: Figmentioning
confidence: 61%
“…We found that two V79 lines obtained from separate sources differed greatly in the size of their dCTP pools and that the line with the large pool (now named V79/dC) lacked the ability to deaminate dCMP. Several earlier reports have demonstrated the absence or low activity of the enzyme dCMP deaminase in hamster cells (4,5,12).…”
Section: Discussionmentioning
confidence: 92%
“…A number of mammalian mutant cell lines possess CTP synthetase activity which is insensitive to inhibition by CTP. As a result, these cell lines display complex phenotypes which include increased intracellular pools of CTP and dCTP (13,14), resistance to nucleotide analog drugs used in cancer chemotherapy (15)(16)(17)(18), and an increased rate of spontaneous mutations (14 -16). In addition, elevated CTP synthetase activity is a common property of leukemic cells (19) and rapidly growing tumors found in liver (20), colon (21), and lung (22).…”
mentioning
confidence: 99%